Biocompatibility of non-precious dental casting alloys : development of novel testing mechanisms - McGinley, Emma Louise (Trinity College (Dublin, Ireland). School of Dental Science, 2011)
The aim of the present investigation was to investigate the biocompatibility potential of commercially available non-precious dental casting alloys facilitated by multiple analyses using a two-dimensional (2D) oral keratinocyte (TR146) cell monolayer structure and a novel three-dimensional (3D) human-derived, full-thickness, differentiated oral mucosal model. The first section of the study aimed to determine the influence of the surface finishing condition of a Ni-based (d.Sign® 10) dental casting alloy on the biocompatibility potential. The biocompatibility was determined following direct and indirect exposure of the dental casting alloys to the 2D oral keratinocyte cell monolayer structures. The clinically relevant polished dental casting alloys induced significantly increased adverse biological effects compared with the ‘as-cast’ alumina particle air abraded alloys. In addition, the study showed that the use of trypsin-edetate disodium (EDTA) was inappropriate in the determination of the TR146 cell density measurements and highlighted difficulties for comparisons with trypsin-EDTA-treated cell density studies in the dental literature. The biocompatibility potential of two polished Ni- based (d.Sign® 10 and d.Sign® 15) and a cobalt-chromium (Co-Cr) (d.Sign®30) dental casting alloy were investigated on the 2D TR146 cell monolayer structure and compared using multiple analyses. The d.Sign® 15 dental casting alloy was shown to elicit significantly increased adverse morphological and physiological responses from the 2D TR146 cell monolayer structures compared with the d.Sign®10 alloy and the Co-Cr (d.Sign®30) alloy. The influence of oral microorganisms (Streptococcus mutans, Candida albicans and Candida dubliniensis) on the biocompatibility potential of the dental casting alloys was also determined using the 2D TR146 cell monolayer structure. Oral microorganisms were shown to enhance the loss of biocompatibility, possibly due to the decreased pH levels, which exacerbated metal ion leachate release levels from the alloys.
Keywords: Dental Science, Ph.D.; Ph.D. Trinity College Dublin